Hydro-aza-(C59 N)fullerenes: Formation Mechanism and Hydrogen Substitution. - Eigler, Regina; Heinemann, Frank Wilhelm; Hirsch, Andreas (Chemistry - A European Journal, 2016)
Azafullerenes are as yet the only synthetically available heterofullerenes. Herein, we present plausible reaction pathways towards pentaaryl azafullerenes, focusing on the reactivity of hydro-azafullerene intermediates and their regiochemistry. The X-ray structure of a β'-hydro-tetraaryl adduct is presented for the first time. The reactivity of dihydro-azafullerene adducts is demonstrated here through H-abstraction in mass spectrometric experiments. Moreover, hydride abstraction and subsequent hydroxylation is possible, as well as deprotonation followed by alkylation.

Investigation of pentaarylazafullerenes as acceptor systems for bulk-heterojunction organic solar cells - Wessendorf, Cordula D.; Eigler, Regina; Eigler, Siegfried; Hanisch, Jonas; Hirsch, Andreas; Ahlswede, Erik (Solar Energy Materials and Solar Cells, 2015)
Keywords: Alternative acceptor; Azafullerene; BHJ solar cell; Organic photovoltaics; Raised LUMO

Selective oxidative conversion of triaryldihydro[C59N] fullerenes: A model case for oxygenation of carbon allotropes - Eigler, Regina; Heinemann, Frank Wilhelm; Hirsch, Andreas (Chemical Communications, 2014)
The photooxidation of triaryldihydro[CN]fullerenes was achieved by treatment with air and light leading to a new selective core functionalization of azafullerenes, which serves as a model case for oxygenation of carbon allotropes. © 2014 The Royal Society of Chemistry.